The Relationship Between Workload and Employee Stress Levels at PT. Aria Consultant Services in The City of Makassar” - Safhira Muchtar, Annisa; Yamin, Muh Nur; Seppa, Yusi Irensi (Universitas Negeri Makassar, 2025)
The purpose of this study is to ascertain the workload, work stress level, and correlation between workload and work stress levels at PT. Aria Consulting Services in Makassar City. This study employs a quantitative methodology, utilizing observational data gathering approaches. surveys and records. Validity testing, reliability tests, normalcy tests, descriptive analysis, and correlation analysis are examples of data analysis procedures. The study's findings demonstrate that each variable's indications indicate that the workload level is in the extremely high range. The degree of stress at work is really high. The SPSS correlation indicates a significant association between the two variables. Thus, it can be said that there is a stronger correlation between PT. Aria Consulting employees' stress levels and their workload.